Spatial patterns of honey bee (Apis mellifera L.) genetic diversity in continental Portugal: the story told by mitochondrial DNA - Pinto, M. Alice (2010)
Over 24 honey bee (Apis mellifera L.) subspecies occur naturally in Europe, Africa and the Middle East. Morphological and molecular markers have grouped this wide-ranging diversity into four lineages (A, M, C, O). The Iberian Peninsula harbours two of such lineages (A and M) and the greatest honey bee maternal diversity and complexity across Europe. While the Spanish honey bee populations have been extensively surveyed for mtDNA variation, the genetic composition of the populations inhabiting the Portuguese side of the Iberian Peninsula is virtually unknown. Herein, we present the first comprehensive account of the maternal variation across continental Portugal. Over 1000 colonies were surveyed for the COI-COII mitochondrial DNA region, which showed a high genetic diversity across Portugal, mostly haplotypes of African origin (lineage A).